Development of Interactive Video Based Powerpoint Media In Mathematics Learning - Zakiyah Anwar; Muhammad Syahrul Kahar; Rais Dera Pua Rawi; NurJannah Nurjannah; Hermanto Suaib; Febrianti Rosalina (Journal of Educational Science and Technology (EST), 2020)
This study aims to determine the effectiveness and practicality of interactive video-based PowerPoint media implemented in learning. This research and development phase refers to the Research and Development (R&D) method. The assessment instruments consist of: (1) Validity instruments in the form of validity assessment instruments based on interactive video PowerPoint media; (2). Practicality instruments in the form of questionnaires for teacher and student responses to interactive video-based PowerPoint media; and (3) Effectiveness instruments in the form of observations of learning outcomes and student learning outcomes. Based on data analysis, obtained an average level of media validity of 3.99 and included in the valid criteria. Also, the practicality test results are seen from the teacher's response to learning by 4.4 and the response of students by 3.46 with practical criteria. This is supported by the results of students' learning tests on the use of interactive video-based PowerPoint media with an average score of students learning outcomes of 70.29. Therefore, it can be concluded that the interactive video-based PowerPoint media developed is effective and practical in the implementation of learning. On the other hand, the development of this media focuses on the concept of integrated learning video learning using PowerPoint and concentrates on interactive learning.